Teknik Cinematherapy dalam Meningkatkan Kedisiplinan Shalat Berjamaah Siswa MAN Palopo - hasyim, baso; Masri, Subekti; Mutakabbir, Abdul; Kasmi, Kasmi (Universitas Muria Kudus, 2022)
The congregational prayers that have been scheduled at MAN Palopo are often not carried out by the students, this means that there have been violations related to student discipline against school rules. To overcome this, this research comes up with offering cinematherapy techniques which aim to improve student discipline in performing congregational prayers. This research was conducted using quantitative methods with a sample of 40 people selected by random sampling. This study reveals that there is an effect of cimematherapy techniques on increasing the discipline of congregational prayer at MAN Palopo MAN students.